Unveiling the Role of the Scramble Model in Enhancing Thematic Learning Outcomes - Purnama, Rahayu Tika; Afrimon, Afrimon; Ratnasari, Lili (Strata Social and Humanities Studies, 2024)
This classroom action research (PTK) is motivated by the low quality of the learning process and learning outcomes. The solution to this problem is the use of the Scramble model. This research aims to describe improving the quality of the learning process and learning outcomes. This classroom action research (PTK) was carried out in class V of SD Negeri 09 Head Bukit in two cycles: planning, implementation, observation, and reflection. The results of the classroom action research conducted by the researcher from July 26, 2023, to August 30, 2023, are as follows. The learning process in cycle I, in the teacher aspect, obtained a percentage of 70% and 75% for students; in cycle II, the teacher aspect obtained a percentage of 83% and students 79%. The student's learning outcomes in the initial conditions in the Indonesian language learning content obtained a percentage of 13%; in cycle I, it obtained 14%, and in cycle II, 100%. In the science learning content in the initial condition, the percentage was 25%; in cycle I, the percentage was 67%, and in cycle II, 95%. Based on the results of this research, it can be concluded that the scramble model can improve the learning process and outcomes of thematic learning in class V of SD Negeri 09 Head Bukit District, Pagu River District, South Solok.